The 10.000-Hour Rule Myth in Sports - Ersin Afacan; Ahmet Uslu (Journal of Educational Issues, 2024)
There are many important controversial issues related to psycho-social areas in sports which involve daily life. One of the controversial topics is the 10.000-hour rule. Indeed, in the book of Malcolm Gladwell entitled “Outliers: The story of success”, the question of “Is the 10.000-hour rule a general rule for success?” is present as a discussion question. It is a problem for scientists to set off from rules rather than theories in the scientific discussions and research related to sportive issues. This situation manifests itself in the subjective measurement of events, phenomena, and objects that should be measured objectively in the first place. In this respect, it is important to identify and describe the issues that harm the scientific perspective of sports. In this regard, the fact that the 10.000-hour rule for success put forward by Malcolm Gladwell is advocated by some sportspeople increases the significance of this study. Therefore, the aim of this study was to make a scientific analysis of the 10.000-hour rule and examine the perspectives of sportspeople. In addition to this, whether the 10.000-hour rule, which has been accepted by limited circles in sports culture, is a myth or not was discussed epistemologically. Document analysis was performed in this descriptive study. As a result, it was determined that the 10.000-hour rule was expressed by limited circles in sports culture and that it had no scientific value. It is recommended to act in accordance with theories and models rather than rules while evaluating sportive events, phenomena, and objects.